Human-bat contacts in the Netherlands, and potential risks for virus exchange - Begeman, L.; Geschiere, M. J. M.; de Boer, W. F.; van den Brand, J. M. A.; Eblé, P. L.; van der Kerkhof, J. H. T. C.; Keur, I.; Lina, P. H. C.; Reusken, C. B. E. M.; de Rosa, M.; Schillemans, M. J.; Schreuder, I.; et al. (One health outlook, 2025)
Background Contacts between people and free-ranging animals have a potential to cause viral disease epidemics when novel viruses are exchanged. The Netherlands has approximately 18 native bat species, of which some generally use buildings for roosting, and has a dense human population. Frequent indirect and direct contacts between bats and humans could thus be expected, however, this has hardly been studied. Methods To study human-bat contacts, people living in the Netherlands were questioned about the type and frequency of their bat contacts, their bat knowledge and perception of bats. For analyses respondents were grouped into (1) general population, (2) bat contact risk group, and (3) people that live in a house with a roost site for a Common Pipistrelle Bat maternity group. Associations between human-bat contacts and other variables were tested by an ordinal logistic regression model. Results We show that 85% (226/265) of group 1 reported no contacts, while 11% (28/265) reported indirect, and 4% (11/265) direct contacts with live bats, dead bats or bat products as their closest type of contacts. These contacts occurred mostly less than yearly. Somewhat similarly, the majority, 69% (9/13) of group 3 reported no contacts, and 15% (2/13) reported indirect contacts and 15% (2/13) reported direct contacts. These occurred monthly to less than yearly. In contrast, a minority, 5% (11/227) in group 2 reported no contacts, while 37% (85/227) reported direct bat contacts, mostly yearly, and 38% (86/227) reported bat-related injury, mostly less than yearly, as their closest type of contact. Overall, an increase in knowledge on bats and bat-related diseases was correlated with closer bat contacts. Conclusions We conclude that even though bats live close to people in the Netherlands, direct contacts between bats, or bat products, and humans are rare in people from the general population, while being common in people involved in bat-related work. Mitigation of human-bat contacts will be most efficient when targeted to specific groups that are likely to have contacts with bats.